Antimicrobial stewardship: widening the collaborative approach - Castro,Sanchez EM; Gilchrist,M; McEwen,J; Smith,M; Kennedy,H; Holmes,A (Journal of Antimicrobial Stewardship, 2017)
Anti microbial stewardship programs (ASPs) would benefit from the participation of nurses to strengthen the increasingly complex mix of clinical, educational, research, organizational and political interventions included within ASPs.